Traditional Chinese medicine health literacy among rural older adults: a cross-sectional study - Zhang, Huizhong; Zhang, Yan; Yan, Yuwen; Li, Xizheng; Tian, Yutong (Frontiers in Public Health, 2024)
The purpose of this study was to understand the current status of traditional Chinese medicine (TCM) health literacy among rural elderly people and its influencing factors.This study used a random number table method to select one prefecture from Henan Province, China, and used a convenience sampling method to select 200 rural older adults who met the inclusion criteria in a township in northern Henan from March to April 2023. A cross-sectional survey was conducted using a general information questionnaire and a traditional Chinese medicine health literacy questionnaire, and the influencing factors of rural older adults were analyzed using univariate analysis of variance and multiple linear regression.The total TCM health literacy score of 200 rural elderly people was 84.14±6.709. One-way ANOVA revealed that six factors, including education level, marital status, type of occupation, presence of family members engaged in medical-related work, main economic sources, and monthly income, influenced the TCM health literacy score of rural elderly people (P<0.05). Multiple linear regression analysis revealed that education level, occupation type, and the presence of family members engaged in medical-related work were the factors influencing the TCM health literacy of rural older adults.The TCM health literacy level of rural elderly people is at the lower to middle level, and health educators should strengthen the publicity and education of TCM health care knowledge for rural elderly people to improve their TCM health literacy level and thus enhance their quality of life.